2021
DOI: 10.1159/000515605
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Brushing and Diagnosis of Pulmonary Nontuberculous Mycobacteria Infection

Abstract: <b><i>Background:</i></b> The optimal bronchoscopy procedure for diagnosis of pulmonary nontuberculous mycobacteria (NTM) infection is unclear. <b><i>Objective:</i></b> This study investigated the usefulness of bronchial brushing in bronchoscopy for diagnosis of pulmonary NTM infection in patients with suspected NTM lung disease and nodular bronchiectasis on chest computed tomography (CT) images. <b><i>Methods:</i></b> Bronchoscopy was pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Fourth, this study included patients with suspected NTM-PD for analysis. Several studies have revealed cases wherein bronchial brushing or washing and repeated culture failed to confirm NTM microbiologically; in some cases, physicians do not proceed with biopsy upon considering the associated risks [ 33 , 34 ]. Therefore, in this study, we included patients with suspected NTM based on CT findings.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, this study included patients with suspected NTM-PD for analysis. Several studies have revealed cases wherein bronchial brushing or washing and repeated culture failed to confirm NTM microbiologically; in some cases, physicians do not proceed with biopsy upon considering the associated risks [ 33 , 34 ]. Therefore, in this study, we included patients with suspected NTM based on CT findings.…”
Section: Discussionmentioning
confidence: 99%
“…Chest high-resolution computed tomography (HRCT) score was reviewed as previously described [ 8 , 9 ]. We divided the lungs into 6 zones at the levels of the carina and inferior pulmonary vein.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 shows the characteristics of all 153 patients. The 3-sputum diagnosed, and non-3 sputum diagnosed groups showed signi cant differences in vs. 19.4(18-21.4); p = 0.002], proportion of patients with MAC treatment history (20.7% vs. 6.5%; p = 0.028), CAT score [11.5(7-18) Chest high-resolution computed tomography (HRCT) score was reviewed as previously described [8,9].…”
Section: Clinical Characteristicsmentioning
confidence: 99%